Aplicación de una auditoría de calidad al área de producción “molinos” en la empresa familia Sancela del ecuador S.A, ubicada en la provincia de Cotopaxi sector Lasso en el período del 01 de enero al 31 de diciembre del 2011 - León Granda, Karla Mercedes (2015)
This research has as main objective to assess compliance with ISO 9001 Quality Standards in Production Area Molinos, to verify procedures and know if they are the right ones for achieving optimum quality. Therefore, this research study establishes the conceptual and scientific basis of Quality Audit, using the methods and techniques such as: interview, survey and observation sheet for real and objective research information. Based on the results achieved determines the need for Audit Quality, the same as that provided to determine the degree of compliance with policies and standards set forth in said area, whose main activity is the transformation of raw material to tissue paper , research will form the basis for quality management department take appropriate steps to correct the detected errors, in order to maintain a quality according to the norms and standards within the company, measures the same as was performed in Production area Molinos based on quality standards in force in Ecuador.